Evaluation of Landscapes and Soundscapes in Traditional Villages in the Hakka Region of Guangdong Province Based on Audio-Visual Interactions - Dongxu Zhang; Hao Chen; Xinyi Zhang; Lingge Tan (Buildings)
Traditional villages in the Hakka region of Guangdong Province have attracted significant attention for their unique cultural heritage and traditional lifestyles. Their favourable audio-visual environments offer immersive and realistic experiences for both residents and visitors. Thus, we selected four representative villages and used semantic segmentation to extract the core visual elements (sky, vegetation, construction, and dynamic) from visual landscape images. Audio-visual interaction experiments and subjective surveys were conducted to investigate the participants’ evaluations of the visual landscape and soundscape to explore the mechanisms of audio-visual interaction. The results revealed that different audio-visual combinations significantly influenced the participants’ visual landscape satisfaction, acoustic comfort, and audio-visual harmony evaluations. Specifically, visual images of natural spaces with a high proportion of sky (24.54%) and vegetation (72.56%), matched with natural sounds (with a sound pressure level of approximately 55 dB) such as birdsong, wind, and flowing water, received excellent ratings for both visual landscape satisfaction and acoustic comfort evaluations. Moreover, the findings further revealed that coordination between visual and audio materials was crucial for enhancing the participants’ perceptions and assessments, highlighting the importance of audio-visual coordination in creating harmonious environments. These findings provide recommendations for spatial planning, landscape design, and soundscape optimisation in traditional villages.